2019
DOI: 10.2174/1872211313666190614151615
|View full text |Cite
|
Sign up to set email alerts
|

Nanosuspension Technology: Recent Patents on Drug Delivery and their Characterizations

Abstract: Background: Nanosuspension has arisen as a remunerative, lucrative as well as a potent approach to improve the solubility and bioavailability of poorly aqueous soluble drug entities. Several challenges are still present in this approach which need more research. The prime aim of this review is to identify such challenges that can be rectified in the future.Methods: Through this review, we enlighten the recent patents and advancement in nanosuspension technology that utilize the different drug moieties, instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 42 publications
(33 reference statements)
0
23
0
Order By: Relevance
“…hence suitable stabilizers/polymers are imparted into nano-suspension to make them stable. The selection of stabilizers is very complicated and challenging as it takes too much time and efforts 60 .…”
Section: Supercritical Fluid Method: Supercritical Fluidmentioning
confidence: 99%
“…hence suitable stabilizers/polymers are imparted into nano-suspension to make them stable. The selection of stabilizers is very complicated and challenging as it takes too much time and efforts 60 .…”
Section: Supercritical Fluid Method: Supercritical Fluidmentioning
confidence: 99%
“…By far, the NanoCrystal ® technology based on WBM approach is the most widely applied technology in the pharmaceutical industry (Goel et al., 2019). Top-down technologies usually apply physical force, such as shear force and impact force to diminish the drug particle size from micro-size to nano-size.…”
Section: Tailor-made Drug Delivery Based On Nanocrystalsmentioning
confidence: 99%
“…Therefore, the development of new techniques to enhance drug solubility remains one of the major research areas in drug discovery and development process 2 . A scan of literature has revealed that numerous attempts has been made to improve the solubility and dissolution of drugs that include cyclodextrins complexes 3 , drug micronization in to amorphous form 4 , prodrug formation 5 , solid dispersion 6,-12 , salt formation 13 , solubilization of drug in solvents, nanoparticles technology 14 , physical modification, nanosuspension [15][16][17][18][19] , modification of crystal habit such as polymorphus, pseudo polymorphous, self-emulsifying drug delivery systems ( SEDDS) 20 , liposomes [21][22][23][24][25] and use of surfactant " micelization" 26 etc. Out of numerous techniques explored so far solid dispersion have been proved to be the most promising strategy to improve the solubility of poorly watersoluble drugs.…”
Section: Introductionmentioning
confidence: 99%